2020
DOI: 10.1177/2475530320910466
|View full text |Cite|
|
Sign up to set email alerts
|

Dosage Adjustments in Patients With Psoriasis on Etanercept: A Retrospective Chart Review

Abstract: Etanercept, 1 of 11 Food and Drug Administration (FDA)–approved biologics used for the treatment for psoriasis, may often be used at off-label dosages. The aim of this retrospective chart review was to determine the frequency of off-label dosing in a single center and the reasons for these deviations as well as the outcomes. The results of this study demonstrated that nearly two-thirds (64.7%) of patients treated with etanercept had some form of dosage adjustment during their treatment course. Dosage increases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The administration of an increased dose while maintaining the interval was the most frequent strategy in the Carrascosa et al [ 7 ] study (80%). In contrast, most patients had a decrease in the dosing interval in the Lee et al [ 21 ] study. In the Egeberg et al [ 16 ] study, the proportion of patients on an escalated dose reduced from 39.0% during the first 24 weeks of treatment to 35.1% during maintenance therapy (25–52 weeks).…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…The administration of an increased dose while maintaining the interval was the most frequent strategy in the Carrascosa et al [ 7 ] study (80%). In contrast, most patients had a decrease in the dosing interval in the Lee et al [ 21 ] study. In the Egeberg et al [ 16 ] study, the proportion of patients on an escalated dose reduced from 39.0% during the first 24 weeks of treatment to 35.1% during maintenance therapy (25–52 weeks).…”
Section: Resultsmentioning
confidence: 96%
“…Long-term data (5 years of treatment) showed that etanercept dose escalations higher than the EMA label were higher at 5 years versus 1 year of treatment (71.4% vs 55.1%) [ 28 ]. All dose escalations in the Lee et al and Esposito et al [ 9 , 21 ] studies were because of inadequate efficacy. In the Lee et al [ 21 ] study, 30% of patients achieved better results with the 50 mg twice weekly dosing versus 25 mg twice weekly and two patients maintained this benefit when they reverted back to the lower dose.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations